2016
DOI: 10.4168/aair.2016.8.3.198
|View full text |Cite
|
Sign up to set email alerts
|

IgG Sensitization to Extracellular Vesicles in Indoor Dust Is Closely Associated With the Prevalence of Non-Eosinophilic Asthma, COPD, and Lung Cancer

Abstract: PurposeRecent experimental evidence shows that extracellular vesicles (EVs) in indoor dust induce neurtrophilic pulmonary inflammation, which is a characteristic pathology in patients with severe asthma and chronic obstructive pulmonary disease (COPD). In addition, COPD is known to be an important risk factor for lung cancer, irrespective of cigarette smoking. Here, we evaluated whether sensitization to indoor dust EVs is a risk for the development of asthma, COPD, or lung cancer.MethodsSerum IgG antibodies ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…This finding indicates the particularly significant role that EVs in indoor dust play in the development of childhood asthma-associated immune responses 35 . Higher serum anti-dust EV IgG antibody levels were also reported in patients with noneosinophilic asthma, COPD, and lung cancer than in healthy controls 14 . Interestingly, adjusted multiple logistic regression showed that the significant increase in anti-dust EV IgG antibody levels in patients with pulmonary disease compared with those in healthy controls was an independent risk factor for asthma, COPD and lung cancer irrespective of more typically associated factors, such as smoking history, age, and sex 14 .…”
Section: Association Between Evs and Pulmonary Diseases Based On Epidmentioning
confidence: 89%
See 3 more Smart Citations
“…This finding indicates the particularly significant role that EVs in indoor dust play in the development of childhood asthma-associated immune responses 35 . Higher serum anti-dust EV IgG antibody levels were also reported in patients with noneosinophilic asthma, COPD, and lung cancer than in healthy controls 14 . Interestingly, adjusted multiple logistic regression showed that the significant increase in anti-dust EV IgG antibody levels in patients with pulmonary disease compared with those in healthy controls was an independent risk factor for asthma, COPD and lung cancer irrespective of more typically associated factors, such as smoking history, age, and sex 14 .…”
Section: Association Between Evs and Pulmonary Diseases Based On Epidmentioning
confidence: 89%
“…Higher serum anti-dust EV IgG antibody levels were also reported in patients with noneosinophilic asthma, COPD, and lung cancer than in healthy controls 14 . Interestingly, adjusted multiple logistic regression showed that the significant increase in anti-dust EV IgG antibody levels in patients with pulmonary disease compared with those in healthy controls was an independent risk factor for asthma, COPD and lung cancer irrespective of more typically associated factors, such as smoking history, age, and sex 14 . Altogether, while research on the impact of bacterial EVs in indoor dust on pulmonary disease is in its early stages, preliminary findings indicate that bacterial EVs pose a serious risk in terms of asthma, COPD, and lung cancer incidence.…”
Section: Association Between Evs and Pulmonary Diseases Based On Epidmentioning
confidence: 89%
See 2 more Smart Citations
“…Pseudomonas aeruginosa often contributes to lung diseases such as cystic fibrosis, and its EVs increase pulmonary inflammation through Toll-like receptor (TLR)2 and TLR4 pathways 67. Moreover, indoor dust, which contains many components of bacteria, has been associated with both Th1 and Th17 responses, which induce neutrophilic pulmonary inflammation 6869. As bacteria-derived EVs can affect distal host cell sites,70 these vesicles might play significant roles throughout the body.…”
Section: Introductionmentioning
confidence: 99%